Digital 3D Scanning of Teeth in Orthodontics - Azad, Gurskaya Narmina (American Journal of Biology and Natural Sciences, 2026)
The prevalence of early tooth extraction among children aged 4 to 7 is quite high and reaches up to 43%. This is a cause of the development of anomalies and deformities of the dentofacial system. Digital 3D scanning of teeth in orthodontics is a modern, accurate, and comfortable method for creating a three-dimensional model of the jaws and teeth using an intraoral scanner, replacing traditional impressions. When choosing a method for fabricating impressions for orthodontic appliances aimed at preserving space in the dental arch, the safety of the procedure and speed are of great importance. An alternative method for obtaining impressions is digital scanning of the dental arches.